Antimicrobial metabolite profiling of Nigrospora sphaerica from Adiantum philippense L. - Kolathuru Puttamadaiah Ramesha; Nagabhushana Chandra Mohana; Bettadapura Rameshgowda Nuthan; Devaraju Rakshith; Sreedharamurthy Satish (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background Endophyte bestows beneficial aspects to its inhabiting host, along with a contribution to diverse structural attributes with biological potential. In this regard, antimicrobial profiling of fungal endophytes from medicinal plant Adiantum philippense revealed bioactive Nigrospora sphaerica from the leaf segment. Chemical and biological profiling through TLC–bioautography and hyphenated spectroscopic techniques confirmed the presence of phomalactone as an antimicrobial metabolite. Results The chemical investigation of the broth extract by bioassay-guided fractionation confirmed phomalactone as a bioactive antimicrobial secondary metabolite. The antimicrobial activity of phomalactone was found to be highest against Escherichia coli by disc diffusion assay. The MIC was found to be significant against both Escherichia coli and Xanthomonas campestris in the case of bacteria and dermatophyte Candida albicans at 150 μg/ml, respectively. Conclusions Overall, the results highlighted the antimicrobial potential of phomalactone from the endophyte Nigrospora sphaerica exhibiting a broad spectrum of antimicrobial activity against human and phytopathogenic bacteria and fungi. This work is the first report regarding the antibacterial activity of phomalactone.